IFRS Implementation in Sri Lankan Unit Trusts Perceptions of Stakeholders Involved in the Implementation Process and Challenges Faced - Ranasinghe, A.; Senaratne, S. (University of Sri Jayewardenepura, Nugegoda., 2014)
At present, unit trusts in Sri Lanka are passing through a stage of rapid growth and are significantly affected by the convergence of local accounting standards with International Financial Reporting Standards (“IFRS Convergence”) brought to effect from January 2012. Hence, this study strives to address the research issues: how the stakeholders of Sri Lankan unit trusts who are directly involved in the preparation of financial reports perceive IFRS Convergence; and the challenges they face in implementing the changes owing to IFRS Convergence. In order to address this issue, the study aims to evaluate perceptions of stakeholders directly involved with preparation of financial reports of unit trusts on IFRS Convergence, and identify and analyse the challenges faced by Sri Lanka‟s unit trusts in implementing changes arising from IFRS Convergence. The study is conducted in the form of a descriptive case study – which describes systems, techniques and procedures used in practice – covering the four stakeholder clusters that are directly involved in the implementation process of International Financial Reporting Standards in unit trusts; namely, Fund Management Companies (FMCs), Trustees, the Institute of Chartered Accountants of Sri Lanka (ICASL) and the Securities and Exchange Commission of Sri Lanka (SEC). When analysing the stakeholder perceptions, the strategic options evaluation model by Johnson et al. (2008) is used, where the strategy of IFRS Convergence is evaluated under the three headings; “suitability” to address key issues relating to the existing position and future direction of the industry/entity; “acceptability” to stakeholders and their expectations; and “feasibility” to execute using the resources and competencies the industry/entity possesses. The study uncovers that the Trustees and FMCs who are directly involved in preparing financial statements, perceive IFRS Convergence to be suitable and acceptable. However Trustees do not regard it feasible, whereas FMCs remain neutral. The ICASL perceives it to be suitable, acceptable and feasible for the unit trust industry, reflecting its role as the promulgator of financial reporting standards. Key implementation challenges faced by FMCs and Trustees are found to be process-related constraints; knowledge constraints; and time constraints. However, ICASL and SEC are not aware of these challenges, highlighting the poor communication between stakeholders.
Keywords: Unit Trusts; IFRS; Perceptions; Challenges